Pathological Changes Due To Helminth Infestation In Goats In Anand District Of Gujarat - Sharma, Subhash; Patel, P.V.; choudhary, Dharmendra; Asopa, Shesh; manohar , Mahendra singh (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The present study describes the gross and histopathological lesion observed due to helminthic infestation by Paramphistomum, Trichuris, Trichostrongylus and Moniezia species in goats in Anand district of Gujarat. The gross lesions comprised mainly rumenitis with shortening of ruminal papillae, catarrhal enteritis with several mature and immature forms of the parasites found in rumen and intestine. Histopathological changes like shortening of rumen papillae, epithelial tissue hyperplasia, edema and fibroblastic proliferation in the sub-mucosa along with the infiltration of the inflammatory cells were observed due to Paramphistomum spp. The histopathological changes due to Trichuris spp. were petechial hemorrhages, necrosis at the tip of villi and proliferation of goblet cells along with the cellular infiltration predominantly lymphocytes, few eosinophils and occasionally macrophages. Also Trichostrongylus spp. and Moniezia spp. were associated with severe histopathological changes like thickening of intestinal wall, infiltration of eosinophils, chronic inflammatory cellular reactions with mucoid degeneration.
Keywords: Histopathological changes; Paramphistomum; Trichuris; Trichostrongylus; Moniezia; cellular infiltration Goats